2018
DOI: 10.1097/nmd.0000000000000779
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder Symptoms and Suicide Risk in Male Firefighters

Abstract: Posttraumatic stress disorder (PTSD) symptoms are positively related to suicide risk among firefighters. One mechanism that may account for this relationship is anxiety sensitivity (AS) cognitive concerns-the fear that cognitive symptoms of anxiety will have catastrophic consequences. We sought to replicate the mediating effect of AS cognitive concerns on the relationship between PTSD symptoms and suicide risk among 214 trauma-exposed male firefighters with non-zero suicide risk. Bootstrap mediation analyses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 55 publications
(71 reference statements)
3
38
0
2
Order By: Relevance
“…AS cognitive concerns are characterized by perceptions that anxiety-related sensations have catastrophic psychological outcomes, such as “going crazy.” Recently, Stanley et al [17] found that AS—specifically, AS cognitive concerns—mediated the relationship between posttraumatic stress disorder symptoms (PTSD) symptoms (cf. anxiety-related sensations) and suicide risk among a sample of female firefighters; this finding was replicated in a sample of male firefighters [18]. In sum, AS cognitive concerns are implicated in increased suicide risk in the context of other psychiatric symptoms, and this effect is also relevant to conceptualizing suicide risk among firefighters.…”
Section: Introductionmentioning
confidence: 84%
“…AS cognitive concerns are characterized by perceptions that anxiety-related sensations have catastrophic psychological outcomes, such as “going crazy.” Recently, Stanley et al [17] found that AS—specifically, AS cognitive concerns—mediated the relationship between posttraumatic stress disorder symptoms (PTSD) symptoms (cf. anxiety-related sensations) and suicide risk among a sample of female firefighters; this finding was replicated in a sample of male firefighters [18]. In sum, AS cognitive concerns are implicated in increased suicide risk in the context of other psychiatric symptoms, and this effect is also relevant to conceptualizing suicide risk among firefighters.…”
Section: Introductionmentioning
confidence: 84%
“…Regarding PTSD rates, deviations were verified-while some studies reported PTSD rates of 26.6% [10] and 31.8% [11] among firefighters, others indicated 13% [12], or even 2.7% [13]. The reasons for a such variation in PTSD prevalence may be related to: the location of data collection, such as when it occurred inside fire departments-due to the lack of homogeneity in samples in relation to the risk faced or, when they are homogeneous, the workplace may inhibit the emotional manifestations [14]; cultural characteristics [15]; or fear of stigma, a common aspect among these professionals [16][17][18][19]. In addition to presenting evidence for the prevalence of PTSD, the symptoms recurrently mentioned by studies were depression (N = 16), alcohol abuse (N = 11), suicidal ideation or behaviors (N = 10) and avoidance (N = 6).…”
Section: Resultsmentioning
confidence: 99%
“…Through this analysis, we identified the main risk and protective factors for the development of PTSD and other stress-related diseases in firefighters as being the perception of stress, social and organizational support, training and experience, usually associated with being a volunteer or professional firefighter, and the choice of coping strategies. These factors influence each other, offering evidence that stress-related diseases are the result of a set of failures that may occur before, during and after potentially traumatic events [12,14,16,27,[29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations